Changes in running speed and step variables measured by inertial sensors during marathon - Enomoto, Y.; Ali, M. J.; Aibara, T.; Nabekura, Y. (ISBS Proceedings Archive (Michigan), 2018)
This study quantified endurance performance for a wide range of running population by measuring running speed and step variables using inertial sensors during marathon. The total of ninety-one runners (71 males and 20 females) participated in this study and step variable data was measured by attaching inertial sensor, developed by Casio, at the sacrum. Runners were classified into sub-groups (3, 4, 5 & 6), based on race time. One-way RM ANOVA witnin sub-groups showed a significant decrease in running speed, step length, and vertical oscillation through the race but step frequency remained stable for most of the runners. The Sub 3 group showed high vertical stiffness in the initial stage of the race but significantly decreased throughout the race. Other groups showed significant decrease in running speed but no significant change in vertical stiffness. It might suggest that good runner could adjust vertical stiffness to keep optimal step length and running speed.